Updated study on multi-TeV cosmic-ray modulation with the Tibet Ⅲ air shower array using the east-west method - 李爱凤 毕效军 陈天禄 陈文益 崔树旺 单增罗布 丁林恺 丁晓红 冯存峰 冯朝阳 冯振勇 苟全补 郭宏伟 郭义庆 何会海 侯正涛 胡海冰 胡红波 黄晶 李万杰 贾焕玉 姜龙 康明铭 乐贵明 雷文华 厉海金 刘成 刘金胜 刘茂元 卢红 孟宪茹 钱祥利 曲晓波 谭有恒 王辉 吴含荣 沈长铨 沈培若 薛良 杨振 袁爱芳 翟留名 张慧敏 张吉龙 张学尧 张勇 张毅 张颖 周勋秀 (Chinese physics C, 2013)
We study the sidereal and solar time modulation of multi-TeV cosmic rays using the east-west method with Tibet air shower array data taken from November 1999 to December 2008. The statistics are twice the amount used in our previous paper. In this analysis, the amplitude of the observed sidereal time modulation is about 0.1%, and the modulation shows an excess from about 4 to 7 hours and a deficit around 12 hours in local sidereal time. The sidereal time modulation has a weak dependence on the primary energy of the cosmic rays. However, the solar time modulation shows a large energy dependence. We find that the solar time modulation is fairly consistent with the prediction of the Compton-Getting effect for high-energy samples （6.2TeV and 12.0TeV）, but exceeds the prediction for the low-energy sample （4.0TeV）. Such a discrepancy may be due to the solar modulation or the characteristics of the experimental device in the near threshold energy.